Prevalence of Pulmonary Embolism and Deep Venous Thromboembolism in Patients With Acute Exacerbation of Chronic Obstructive Pulmonary Disease: A Systematic Review and Meta-Analysis - Han, Weihong; Wang, Minghang; Xie, Yang; Ruan, Huanrong; Zhao, Hulei; Li, Jiansheng (Frontiers in Cardiovascular Medicine, 2022)
Background: Acute exacerbation of chronic obstructive pulmonary disease (AECOPD) increases the risk of pulmonary embolism (PE) and deep venous thrombosis (DVT). AECOPD combined with PE and DVT poses challenges for treatment and management. This necessitates prevention and management to estimate the overall prevalence of PE and DVT among AECOPD patients and to identify the risk factors. Methods: We searched the PubMed, Embase, and Cochrane Library databases from their inception to January 9, 2021 and extracted the data from the included studies. The risk of bias was assessed for each study. We separately calculated the prevalence of PE and DVT in AECOPD patients. Subgroup analysis and meta-regression analyses were performed to determine the sources of heterogeneity. Furthermore, we assessed the publication bias. Results: The meta-analysis included 20 studies involving 5,854 people. The overall prevalence of PE and DVT among AECOPD patients was 11% (95% CI: 0.06-0.17) and 9% (95% CI: 0.06-0.12), respectively. Subgroup analysis demonstrated that the prevalence of PE among AECOPD patients was 12%, 2%, 7%, and 16% in the European, South-East Asia, Western Pacific, and Eastern Mediterranean regions, respectively, and the DVT was 10%, 9%, 9%, and 4%, respectively. The prevalence of PE among AECOPD patients aged ≥70 and <70 years was 6% and 15%, respectively, and the DVT was 8% and 9% respectively. The prevalence of PE among AECOPD patients diagnosed within 48 hours and other times (beyond 48h or not mentioned) was 16%, and 6 % respectively, and DVT was 10% and 7%, respectively. Conclusion: The pooled prevalence of PE and DVT among AECOPD patients were insignificantly different between different age groups and World Health Organization regions. However, early diagnosis was associated with a higher prevalence of PE. Clinicians and the public need to further improve the awareness of prevention and management for PE and DVT among AECOPD patients.